Suicide Clusters: A Review of Risk Factors and Mechanisms. - Haw, C; Hawton, K; Niedzwiedz, C; Platt, S (2012)
Suicide clusters, although uncommon, cause great concern in the communities in which they occur. We searched the world literature on suicide clusters and describe the risk factors and proposed psychological mechanisms underlying the spatio-temporal clustering of suicides (point clusters). Potential risk factors include male gender, being an adolescent or young adult, drug or alcohol abuse, and past history of self-harm. However, the majority of studies lack methodological rigor. Many different psychological mechanisms are described, including contagion, imitation, suggestion, learning, and assortative relating, but supporting empirical evidence is generally lacking. More scientifically rigorous studies are needed to improve understanding of suicide clusters.